By His Excellency William Shirley, Esq ; ... A proclamation for the encouragement of voluntiers to prosecute the war against the St. John's & Cape-Sable's Indians : Whereas the Indians of the Cape-Sable's and St. John's tribes have by their violation of their solemn treaties ... Given at the Council chamber in Boston, on Friday the second day of November, 1744 (Printed by John Draper, printer to His Excellency the governour and Council, 1744)
November 2, 1744 Governor William Shirley's Proclamation for the encouragement of volunteers to prosecute the war against the St. John and Cape Sable's Indians, and various incentives.